The new United Nations approach to sustainable development post-2015: Findings from four overviews of systematic reviews on interventions for sustainable development and health - Luiz A. C. Galvão; Michelle M. Haby; Evelina Chapman; Rachel Clark; Volney Magalhães Câmara; Ronir Raggio Luiz; Francisco Becerra-Posada
ABSTRACT Objective To identify reported interventions that facilitate sustainable development and have had a positive impact on health in four areas: sustainable food production; sustainable energy use; sustainable jobs ("decent work"); and prevention of toxic exposure to chemicals. Methods Systematic review methods were used to synthesize evidence from multiple systematic reviews and economic evaluations. A comprehensive search was conducted of at least 14 databases and 8 websites for each of the four overviews, using pre-defined protocols, including clear inclusion criteria. To qualify as "sustainable," interventions needed to aim (explicitly or implicitly) to positively impact at least two dimensions of the integrated framework for sustainable development and had to include measures of health impact. Results In total, 47 systematic reviews and 10 economic evaluations met the inclusion criteria. The most promising interventions, such as agricultural policies, were identified for each of the four topics. While the evidence for the interventions is not strong because of the limited number of studies, there is no evidence of a definite negative impact on health. The only possible exception is that of taxes and subsidies-though this intervention also has the potential to be pro-equity with higher relative impacts for lower income groups. Conclusions The evidence found for effective interventions is useful for guiding countries toward the best options for non-health sector interventions that can positively impact health. This overviews shows that intersectoral work benefits every sector involved.